2014
DOI: 10.2134/agronj13.0296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Field Management Strategies for Preventing Iron Deficiency Chlorosis in Soybean

Abstract: Iron deficiency chlorosis (IDC) is a serious management issue for soybean [Glycine max (L.) Merr.] grown on calcareous soils. Strip trials were established on calcareous Mollisols to study the effects of Fe-ethylene diamine-N,N¢-bis (hydroxy phenyl) acetic acid (EDDHA) in-furrow (IF-Fe) and of an oat (Avena sativa L.) companion crop on two soybean varieties either tolerant or susceptible to IDC. The severity of IDC varied from low to severe within sites. The susceptible variety produced the highest yield in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…In this study, a logistic equation analysis indicated that the classification of soybean genotypes with differential tolerance to Fe deficiency is relative and not absolute in accordance with the study conducted by Liesch et al (2011). The ability of plants to withstand stress is determined not only by their own characteristics but also by the stress level (Kaiser et al, 2014).…”
Section: Interaction Between Genotypic Tolerance and Soybean Growth Usupporting
confidence: 77%
“…In this study, a logistic equation analysis indicated that the classification of soybean genotypes with differential tolerance to Fe deficiency is relative and not absolute in accordance with the study conducted by Liesch et al (2011). The ability of plants to withstand stress is determined not only by their own characteristics but also by the stress level (Kaiser et al, 2014).…”
Section: Interaction Between Genotypic Tolerance and Soybean Growth Usupporting
confidence: 77%
“…Overall, considering both soil test DTPA‐Fe and soluble salts (electrical conductivity) when screening varieties for chlorotic iron deficiency symptoms in the North‐Central region was recommended (Hansen et al., 2003). This is consistent with other Minnesota research reporting that yield of iron‐deficiency‐susceptible varieties was correlated with soil pH, DTPA‐Fe, electrical conductivity, and soil organic matter at a 6‐inch depth (Kaiser et al., 2014). With such dynamic soil properties influencing iron availability, optimizing iron nutrition is difficult and, in most cases, utilizing practices that inform the 4Rs such as soil tests, plant analysis, and yield maps together when putting a plan together pays dividends.…”
Section: R Management Of Ironsupporting
confidence: 91%
“…Overall, considering both soil test DTPA-Fe and soluble salts (electrical conductivity) when screening varieties for chlorotic iron deficiency symptoms in the North-Central region was recommended (Hansen et al, 2003). This is consistent with other Minnesota research reporting that yield of iron-deficiency-susceptible varieties was correlated with soil pH, DTPA-Fe, electrical conductivity, and soil organic matter at a 6-inch depth (Kaiser et al, 2014). With such dynamic soil properties influencing iron availability, optimizing iron nutrition is difficult and, in most cases, utilizing practices that inform the 4Rs such as soil tests, plant analysis, and yield maps together when putting a plan together pays dividends.…”
Section: R Management Of Ironsupporting
confidence: 85%
“…Iron fertilizers protected with an organic chelate can be effectively applied to soils to correct plant deficiencies. Chelated fertilizers such as Fe-EDDHA (Kaiser et al, 2014;Gamble et al, 2014) have been used with reasonable effectiveness, but their cost may be prohibitive for whole-field applications. Gamble et al (2014) found a soybean yield increase Iron deficiency in maize.…”
Section: R Management Of Ironmentioning
confidence: 99%
See 1 more Smart Citation